Systemic treatment of AIDS-related Kaposi sarcoma: Current status and perspectives - Vanni, Tazio; Sprinz, Eduardo; Machado, Marcelo Warlet; Santana, Rodrigo de C.; Fonseca, Benedito Antonio L.; Schwartsmann, Gilberto (Cancer treatment reviews, 2006)
Kaposi’s sarcoma (KS) is the most frequent type of cancer in patients with Acquired Immune Deficiency Syndrome (AIDS). In the western world, its incidence decreased dramatically in the era of highly active anti-retroviral therapy (HAART). In contrast, the incidence of KS has been steadily climbing in parallel with the AIDS epidemic in Africa over the past 10–15 years, being the most common cancer in adult men in countries like Uganda and Zimbabwe. AIDS–KS can be diagnosed at any stage of HIV infection, although it more commonly occurs in the setting of severe immune suppression, especially with an elevated viral load. Up to now, AIDS–KS is still an incurable disease. Its clinical course is variable, ranging from very indolent cases, requiring no or minimal therapy, to a rapidly progressive disease. Various local therapies are available to control small and asymptomatic lesions, while cytotoxic, immunological and biological therapies can be considered for more aggressive disease. The primary goal of therapy in most of the cases is to provide safe and effective palliation, in order to quality of life. Optimal anti-retroviral therapy is a key component of AIDS–KS management. There are still many questions to be answered in the management of patients with AIDS–KS, such as (1) What are the therapeutic agents that should be used in this disease, and in which sequence? and (2) What are the benefits and risks expected with each treatment option? The aim of this review is to discuss the systemic management of AIDS–KS, with special focus on the above mentioned questions.